The Potential of Stress Management Training as a Coping Strategy for Stressors Experienced in Theater of Operation: A Systematic Review - Bouchard, Stéphane; Guitard, Tanya; Laforest, Mylène; Dumoulin, Stéphanie; Boulanger, Julie; Bernier, François (IntechOpen, 2012)
None